2018
DOI: 10.1097/dbp.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Dynamics of Household Food Insecurity Impact Children's Developmental Outcomes

Abstract: Based on a novel food insecurity transitions framework and examination of multiple developmental outcomes, this study highlights the importance of examining both depth and transitional dynamics of food insecurity. Findings indicate that DeepenFIS and PersistMFIS may have potentially the most harmful effects on children's developmental outcomes. Clinically, findings support the need for addressing food insecurity in early childhood, even if the food insecurity challenges are marginal and just emerging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 30 publications
2
54
0
Order By: Relevance
“…We hope to add to the literature in four main ways: first, we provide robust evidence on the relationship between the timing and duration of household food insecurity during childhood and learning outcomes at adolescence in a key emerging economy. Evidence from the US suggested that, as in the case of income poverty, household food security is more often a transient rather than a permanent condition, with the majority of households moving in and out of food insecurity over time (Burke et al, 2017;Grineski et al, 2018;Howard, 2011;Perez-Escamilla & Pinheiro de Toledo Vianna, 2012). Whether a similar dynamic pattern holds in India-where, proportionally speaking, the scale and depth of food insecurity is greater-and what the implications of this dynamics for adolescent learning are, has been, so far, unclear.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…We hope to add to the literature in four main ways: first, we provide robust evidence on the relationship between the timing and duration of household food insecurity during childhood and learning outcomes at adolescence in a key emerging economy. Evidence from the US suggested that, as in the case of income poverty, household food security is more often a transient rather than a permanent condition, with the majority of households moving in and out of food insecurity over time (Burke et al, 2017;Grineski et al, 2018;Howard, 2011;Perez-Escamilla & Pinheiro de Toledo Vianna, 2012). Whether a similar dynamic pattern holds in India-where, proportionally speaking, the scale and depth of food insecurity is greater-and what the implications of this dynamics for adolescent learning are, has been, so far, unclear.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Research on children's experiences of food insecurity at home in high-income countries-particularly the US-has suggested that household food insecurity has wide-ranging implications for child school participation, learning and broader development. The timing of food insecurity and its persistence during sensitive periods of childhood may also be associated with poorer educational outcomes (Alaimo, Olson, & Frongillo, 2001;Grineski, Morales, Collins, & Rubio, 2018;Howard, 2011;Jyoti, Frongillo, Jones, & Al, 2005). However, there is a serious dearth of research on the learning consequences of household food insecurity, particularly around its timing and persistence over childhood, in LMIC settings.…”
Section: Introductionmentioning
confidence: 99%
“…People from food-insecure households, for example, tend to report poorer physical health [3][4][5], symptoms of anxiety or depression [6,7], lower self-esteem [8], and poorer overall mental health status [9,10]. Particularly, children who live in food-insecure homes are more likely to have emotional distress, decreased quality of life, and worse academic performance [11][12][13][14]. Annually, food insecurity has caused at least 160 billion dollars of economic burden in the USA [15].…”
Section: Introductionmentioning
confidence: 99%
“…Food insufficiency/insecurity has a limited but growing literature, showing a link with academic achievement in older U.S. children (e.g., poorer math scores, poorer reading scores, grade repetition [ 53 , 54 , 56 ]), and EF is closely related to these outcomes [ 26 , 50 ]. Further, previous literature that has directly assessed the concurrent and long-term impacts of food insecurity on EF in preschool-aged (3–5) and early elementary-aged children (6–7) has found that global and domain-specific EFs are significantly negatively impacted when children are exposed to any degree of food insecurity [ 57 , 58 ]. Specifically, one of these studies found that any exposure to any level of food insecurity (either marginally insecure or completely food insecure) in either kindergarten or first grade resulted in worse working memory and cognitive flexibility, two components of EF [ 57 ].…”
Section: Discussionmentioning
confidence: 99%